HIV; Is It Now An Epidemic - Nida Sajid; Karim Kammerudin (ziauddin University, 2024)
Background: An HIV positive individual from nontraditional background presented with abdominal lymphadenopathy. The human immunodeficiency virus (HIV) is a lenti virus (a subgroup of retrovirus) that causes HIV infection and AIDS (acquired immunodeficiency syndrome).AIDS is a condition in which progressive failure of the immune system allows life threatening opportunistic infections and malignancies. Methods: We present a case of 40yrs male, who presented with abdominal pain, vomiting and diarrhea accompanied with weight loss. Laboratory data shows pancytopenia, raised lactate dehydrogenase, CT scan abdomen reports; multiple enlarged lymph nodes along celiac trunk, mesenteric vessels, para-caval, aorto-caval, peri-pancreatic regions respectively. Results: Findings were suggestive of lymphoma. His HIV antibody (on ELISA) was positive and he was advised to be followed it up by western blot technique. Conclusion: This case report suggest that even a person not belonging to a traditional high risk group can have HIV and its complications such as lymphoma. Key Words: Human immunodeficiency virus, acquired immunodeficiency syndrome, vomiting, diarrhea, weight loss.